The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1097/00000658-198208000-00008
|View full text |Cite
|
Sign up to set email alerts
|

CEA Monitoring Among Patients in Multi-institutional Adjuvant G.I. Therapy Protocols

Abstract: The Gastrointestinal Tumor Study Group (GITSG) has since 1975 included protocols for monitoring carcinoembryonic antigen (CEA) levels in its colorectal cancer adjuvant trials. Among the 563 patients on the colon cancer study (GI 6175) and the 207 patients on the rectal cancer study (GI 7175), one third had preoperative CEA determinations and more than 90% had some postoperative CEA monitoring. Colon cancer patients whose preoperative CEA was greater than 5 ng/ml had a greater probability of recurring than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1
3

Year Published

1983
1983
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(46 citation statements)
references
References 11 publications
2
40
1
3
Order By: Relevance
“…The majority of studies evaluating preoperative CEA levels reveal it to be an independent prognostic factor after surgical resection for colorectal cancer [1][2][3][4][5][6][7][8]10], although some contradictory studies reported that the CEA level is a predictor for survival [12][13][14][15][16]. We concur with this and confirmed a preoperative elevation in serum CEA as an independent prognostic factor for both 5-year overall and disease-free survival in this analysis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The majority of studies evaluating preoperative CEA levels reveal it to be an independent prognostic factor after surgical resection for colorectal cancer [1][2][3][4][5][6][7][8]10], although some contradictory studies reported that the CEA level is a predictor for survival [12][13][14][15][16]. We concur with this and confirmed a preoperative elevation in serum CEA as an independent prognostic factor for both 5-year overall and disease-free survival in this analysis.…”
Section: Discussionsupporting
confidence: 85%
“…Many studies have demonstrated the prognostic value of the preoperative CEA level after surgical resection of colon and rectal cancer, but whether the preoperative CEA level is an independent prognostic variable in colon cancer has remained controversial [12][13][14][15][16]. Therefore, the aim of this study was to assess the prognostic value of the preoperative serum CEA level in patients with colon cancer.…”
Section: Introductionmentioning
confidence: 98%
“…A more critical examination restricted to 563 patients with Dukes stage B or C tumours undergoing curative resection found that a raised pre-operative CEA only had a significant effect on prognosis in Dukes C lesions of the colon but not of the rectum (Steel et al, 1982 (Bradwell et al, 1979), and cancer of the cervix (Te Velde et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognostic significance of slightly raised levels of CEA is still debatable (Goslin et al, 1980;Blake et al, 1982;Steel et al, 1982). A combination of CEA and acute phase reactant proteins (APRPs) have been used in the pre-operative assessment of stomach cancer (Rashid et al, 1982) and colorectal cancer (Ward et al, 1977) and their value assessed by multivariate analysis.…”
mentioning
confidence: 99%
“…Moertel et al reported its independent prognostic value only in patients with involvement of four or more lymph nodes (34). Different results were observed in the trial of Gastrointestinal Tumor Study Group: s-CEA affected survival of patients with one to four positive nodes (35). Moreover, Wang et al in another study concluded that prediction of significant outcomes persisted for patients analysed separately at Astler-Coller stage C1 (lack of tumor penetration beyond the bowel wall) and C2 (presence of penetration) (36).…”
Section: Discussionmentioning
confidence: 97%